Ideas about the criteria of the Ecumenical Council in Byzantium in the 1st half of the 15th century and the concept of the Pentarchy - Petr Paskov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article examines the views of Byzantine theologians and church leaders of the 1st half of the 15th century on the criteria for an Ecumenical Council in connection with the controversy about the Union of Florence. The consideration also includes the ecclesiological tradition of the previous century, reflected in the documents of negotiations with Rome on church union and anti-Latin writings of Archbishop Nilus Cabasilas. It also briefly examines the results of Byzantine theological development, formulated in the first decades of Ottoman rule. The author shows that Orthodox theologians of the late Byzantine period, following a tradition dating back to the 1st millennium, did indeed recognize (contrary to popular beliefs) the existence of strict formal canonical criteria for the Ecumenical Council, which were defined in their eyes by the concept of the «Pentarchy» of the ancient Patriarchs: Council could be considered Ecumenical if it was recepted by representatives of the Churches of Rome, Constantinople, Alexandria, Antioch and Jerusalem. At the same time, other local Churches were assigned a secondary role. The significance of individual bishops was completely leveled out; the subject of church activity was the Patriarchy. This system of ecclesiological concepts by the 15th century already to some extent did not meet the requirements of reality; nevertheless, thanks to its collegial character, it gave the Orthodox Church the means to overcome the crisis caused by the Union of Florence. The rejection of those teachings of the Roman Church, in which it deviated from Orthodox dogma, on the part of the patriarchs of Alexandria, Antioch and Jerusalem, their rejection of the union (confirmed, among other things, conciliarly in Jerusalem in 1443) and the support of its opponents in the Patriarchate of Constantinople played in this process defining role. Due to this, the Council of Ferrara-Florence could not be considered Ecumenical from the point of view of the Byzantine tradition. At the same time, the development of ecclesiological thought in the 15th century. strengthened Orthodox theologians in the conviction that an Ecumenical Council was possible without the participation of Rome. The «Pentarchy» thus passed into the «Tetrarchy».